Endoscopic Stapedotomy: A Systematic Review. Issue 10 (9th December 2021) - Hoskison, Emma E.; Harrop, Elizabeth; Jufas, Nicholas; Kong, Jonathan H. K.; Patel, Nirmal P.; Saxby, Alexander J.
Abstract : Objectives: Stapes surgery has evolved from its origins in 1956. Microscopic assisted stapedotomy remains the most common technique but the introduction of endoscopic ear surgery has led to some units using this new approach. The endoscope delivers a wide angled, contextual view of the stapes, and associated pathology. This systematic review provides a critical analysis of the current published endoscopic data, allowing comparison to the established microscopic technique. Data sources: Six databases (PubMed, Medline, Cochrane database, AMED, EMBASE, and CINAHL) were searched for studies within the last 10 years. Study selection and data extraction: English language articles including 5 or more cases were included. Primary outcomes included audiological results and reported complications. Data was extracted according to PRISMA guidelines. Results: Thirteen papers were identified comprising 361 endoscopic stapes surgeries. Postoperative temporary facial nerve weakness was reported in 3 patients (0.8%) which all resolved within 4 weeks. Chorda tympani injury occurred in 21 cases (5.8%) and vertigo in 61 (16.9%). The audiometric outcomes of endoscopic stapes surgery were available for 259 patients and showed air bone gap closure rates of 71.4% (0–10 dB), 25.9% (11–20 dB), 2.3% (21–30 dB), and 0.4% (>30 dB). Conclusions: Endoscopic stapes surgery has similar audiometric outcomes compared to the traditional microscopic approach with air bone gap closure values of <20 dB in 97.3% of cases. However, the complication rates of chorda tympani damage, postoperative dysguesia, and tympanic membrane perforation for endoscopic stapes surgery are high. Caution should therefore be taken before undertaking stapes surgery with the endoscopic technique. Further studies are required to prove superiority over well established existing microsurgical methods.